4‐Nitro‐3‐(5‐tetrazole)furoxan and Its Salts: Synthesis, Characterization, and Energetic Properties. Issue 44 (17th September 2013) - Liang, Lixuan; Wang, Kai; Bian, Chengming; Ling, Liming; Zhou, Zhiming
Abstract A series of new energetic salts based on 4‐nitro‐3‐(5‐tetrazole)furoxan (HTNF) has been synthesized. All of the salts have been fully characterized by nuclear magnetic resonance (1H and 13C), infrared (IR) spectroscopy, elemental analysis, and differential scanning calorimetry (DSC). The crystal structures of neutral HTNF (3) and its ammonium (4) and N‐carbamoylguanidinium salts (9) have been determined by single‐crystal X‐ray diffraction analysis. The densities of 3 and its nine salts were found to range from 1.63 to 1.84 g cm−3. Impact sensitivities have been determined by hammer tests, and the results ranged from 2 J (very sensitive) to >40 J (insensitive). Theoretical performance calculations (Gaussian 03 and EXPLO 5.05) provided detonation pressures and velocities for the ionic compounds 4–12 in the ranges 25.5–36.2 GPa and 7934–8919 m s−1, respectively, which make them competitive energetic materials.